1998
DOI: 10.1097/00007632-199812010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Nucleus Pulposus on Blood Flow and Endoneurial Fluid Pressure in Rat Dorsal Root Ganglia

Abstract: Application of nucleus pulposus to nerve root increased endoneurial fluid pressure and decreased blood flow in the dorsal root ganglia. This study's acute observations in the dorsal root ganglia may thus help to explain why disc herniations without compression of neural tissue are sometimes painful because similar pathologic findings are observed after only nucleus pulposus application to the nerve root. The authors further suggest that exposure of nerve roots to nucleus pulposus may establish a "compartment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 37 publications
0
58
0
4
Order By: Relevance
“…Such intraneural edema is associated with a reduction in nerve blood flow [15]. Yabuki et al [30] harvested autologous nucleus pulposus and applied it to the nerve root just proximal to the DRG, with continuous monitoring of the blood flow using a laser Doppler flow probe. They reported that application of nucleus pulposus to the nerve root decreased blood flow in the dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Such intraneural edema is associated with a reduction in nerve blood flow [15]. Yabuki et al [30] harvested autologous nucleus pulposus and applied it to the nerve root just proximal to the DRG, with continuous monitoring of the blood flow using a laser Doppler flow probe. They reported that application of nucleus pulposus to the nerve root decreased blood flow in the dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, ultrastructural changes such as swelling of Schwann cells were demonstrated using electron microscopy [34]. The capacity of nucleus pulposus to induce both structural and functional changes in spinal nerve roots has been verified in several recent studies evaluating the biologic effects of nucleus pulposus [1,3,4,20,21,22,35,38,39,44,47,52]. Nucleus pulposus' role in pain induction has recently been evaluated [22,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal nerve root injury can be induced by chronic compression and/or the presence of nucleus pulposus [1, 3, 4, 5,20,21,22,26,31,32,33,34,35,36,37,38,39,46,52]. It has been demonstrated experimentally that epidurally applied autologous nucleus pulposus, without any compression, can induce significant changes in nerve root morphology and function in animal models [4, 5,21,22,31,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…In animals and humans, pure compression of a non-inflamed nerve produces sensory and motor changes without pain, whereas pain is elicited with manipulation of an inflamed nerve [1,2]. The effects induced by the contact of the NP with the epidural elements have been observed in experimental studies and compelling evidence of histological alterations, changes in the nervous electrical activity, and in the intraneural blood flux after such contact has been obtained [2][3][4][5][6]. The NP structure mainly comprises proteoglycans, collagen and support cells, which are able to produce inflammatory mediators after injury, such as cytokines [7].…”
Section: Introductionmentioning
confidence: 99%